Ofsted's judgement of parental engagement: A justification of its place in leadership and management. (October 2015) - Goodall, Janet
This article considers the recent change to Ofsted's inspection criteria, which now includes a judgement on schools' engagement with parents as part of the overall Leadership and Management judgement. The article argues that this is the correct place for this judgement, linking effective parental engagement with the development of a broad and holistic understanding of parental engagement, and with the creation of ethos in the school.